A novel oxygen-sensitive potassium current in rat carotid body type I cells. - Buckler, K (1997)
1. Hypoxic stimuli depolarize carotid body type I cells causing voltage-gated calcium influx. This study investigates the cause of this membrane depolarization. Isolated type I cells from neonatal (11-16 day) rat carotid bodies were used in the experiments. 2. Tetraethylammonium (TEA; 10 mM), 1 and 5 mM 4-aminopyridine (4-AP) and 20 nM charybdotoxin all failed to evoke a significant rise in [Ca2+]i. Similarly, in perforated patch whole-cell recordings, a combination of 10 mM TEA and 5 mM 4-AP failed to depolarize type I cells. 3. In type I cells voltage clamped at -70 mV, anoxia evoked a small inward current under control conditions, but had no effect in the absence of pipette and extracellular K+. 4. Anoxia decreased resting membrane conductance from 322 to 131 pS. The anoxia-sensitive current (measured using voltage ramps from -100 to -40 mV) had a reversal potential of -89 mV in 4.5 mM Ko+ and -66 mV in 20 mM Ko+, indicating that this current was carried principally by potassium ions. In contrast, 10 mM TEA + 5 mM 4-AP had little effect on the current-voltage relationship of the cells over the same range. 5. This O2-sensitive K+ conductance showed only mild outward rectification over the range -90 to +30 mV, which could be approximated by the Goldman-Hodgkin-Katz current equation. In addition, there was no time-dependent activation or inactivation of membrane currents elicited by voltage steps in the range -100 to -30 mV. 6. The O2-sensitive K+ conductance was inhibited by graded reductions in PO2 to 40 Torr and below, with a K1/2 of about 12 Torr. 7. The data suggest that hypoxia depolarizes type I cells principally through the inhibition of a small voltage-insensitive resting (or background) K+ conductance, and not through the inhibition of voltage-gated TEA and 4-AP-sensitive K+ channels (e.g. maxi-K or KO2 channels), as has been previously suggested.